A linguistic awareness intervention targeting spelling and written expression in a 10-year-old dyslexic child - Niolaki, Georgia; Vousden, Janet; Terzopoulos, Aris; Taylor, Laura; Masterson, Jackie (Preschool and Primary Education, 2021)
We report the case of a monolingual English-speaking boy (AM) aged 10-years, and the intervention targeting spelling and written expression difficulties that AM had. AM’s performance was contrasted in all experimental measures to a group of 13 typically developing spellers attending the same class. Literacy and cognitive assessments revealed for AM non-word reading difficulties, and deficits in spelling, written expression, phonological ability, verbal memory and rapid automatized naming. AM took part in nine sessions of linguistic awareness intervention that focused on promoting simultaneous attention to phonology, orthography, morphology, semantics and syntax. Results revealed a significant improvement in spelling, non-word reading, writing and handwriting. The results indicate that raising linguistic awareness can have a robust impact on spelling and written expression.